Innovation and employment: a survey - Marco Vivarelli (Institute for the Study of Labor (IZA), 2007)
According to the compensation theory, market forces should assure a complete compensation of the initial labour-saving impact of process innovations. In this paper a critique of this approach is proposed through a detailed survey of the theoretical and empirical literature on the subject. The general conclusion is that - although compensation is always working - the complete counter-balancing of dismissed workers cannot be assumed ex-ante.
urn:nbn:de:101:1-2008042202
Keywords: 330; Innovation; Technischer Fortschritt; Personalabbau; Beschäftigungseffekt; Kritik; Theorie; Welt